A Retrospective Cohort Study of 23 Cases of Inter Trochanteric Femur Fracture in Elderly Patients Treated with Dynamic Hip Screw (DHS) without Image Intensifier (Journal of Pakistan Orthopaedic Association, 2020)
Objective: To determine the clinical and radiological outcome of the inter trochanteric femur fractures in elderly patients fixed with Dynamic Hip Screw( DHS) without image intensifier.Methods: This retrospective cohort study was conducted in Department of Orthopaedics Bolan Medical Complex hospital Quetta from 25th November 2017 to 23rd November 2019.The medical records of inter trochanteric fractures fulfilling the inclusion criteria who were operated for DHS without image intensifier were analyzed retrospectively. The screw placement technique, post operative position of lag screw in radiographs, union and complications were noted in each case.Results: The records of 23 patients with mean age 75 ±7 years(range 58 to 90 years) were analyzed. Male patients were 15(65.2%) and female 8(34.7%). The position of lag screw was central position in 14(60.8%) patients and posterior inferior in 4(17.3%) patients while in 5(21.7%) patients the screw was in anterio superior position. Fracture union was noted in 22(95.6%) patients and implant failure in 1(4.3%) patient.Conclusion: DHS under image intensifier should be the gold standard treatment of intertrochanteric fractures. However, acceptable radiographic position of DHS lag screw in femoral head and neck and ultimate union can be achieved in selected inter trochanteric fractures fixed without image intensifier. However experience of the operating surgeon and accurate preoperative templating and per operative lag screw placement techniques are mandatory.